(untitled) (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has rapidly transformed multiple sectors, promising greater efficiency, innovation, and personalized services. However, the rise of AI presents significant concerns related to fairness, equity, and social justice. As AI systems become increasingly integrated into everyday life, there is a pressing need to ensure that these technologies promote fair access and opportunities for all, particularly marginalized communities. This paper examines the role of AI in promoting social justice, focusing on issues such as algorithmic bias, accessibility, and discrimination in AI-driven systems. The study investigates current practices in AI development and deployment, exploring their implications on social justice and proposing solutions to ensure that AI benefits all segments of society. By integrating empirical evidence, case studies, and theoretical frameworks, the paper provides a comprehensive overview of how AI can be designed to promote equity, inclusivity, and social justice. The findings highlight the need for a responsible AI framework that prioritizes diversity, inclusivity, and transparency in AI development processes.